3D printing of individualized cranial PEEK implants – saving costs and following regulatory pathways (Transactions on Additive Manufacturing Meets Medicine, 2021)
This paper describes of a complete workflow to produce individualized cranial implants using additive manufacturing with PEEK filament. The workflow includes design regulations, definitions of part orientation and support generation as well as process parameter definitions and post-processing steps. In addition to technical feasibility, clinical requirements and regulatory pathways are described. The described workflow has the potential to accelerate the distribution of personalized medical care while saving material compared to milling processes. In comparison to milling technologies this manufacturing process has the enormous potential to save raw material. In additive manufacturing about 85% of the material used is used for the implant. Only 10-15% is used for support structures, which are removed in post-processing. However, with conventional manufacturing technologies such as milling, on the other hand, about 10-20% of the material is used as the implant - the rest is wasted that is removed. In addition, the described technology provides for the first time to achieve mechanical properties equivalent to those achieved by milling. Cost savings with filament printing compared to other 3D printing technologies for cranial plate manufacturing will further accelerate the acceptance of patient matched implants. Comparable low initial investments in printer hardware and reduced post-processing requirements make the overall costs shrink in comparison to titanium printing based on powder bed technology. Kumovis workflow makes individualized cranial implants affordable for a broad range of healthcare systems.  In addition, it accumulates the clinical benefits of high-performance polymers such as high wearing comfort, patient`s acceptance, millimetre accuracy of fit, optimal biocompatibility and low revision rates.
Keywords: additive manufacturing; PEEK; cranial implant; neurosurgery; cmf; polymer printing; 3D printing; 3D-printing; MDR; cranioplasty; PSI; PMI; patientspecific; patient-specific; patientmatched; patient-matched; cost saving; healthcare; individualized